Arithmetic Review

Evaluating Expressions

Simplify Expressions

Exponential Expressions

Factoring Polynomials

Factoring Part 2

Factoring Special Cases

Solving Equations

Translating into numerical expressions

Inequalities

Rational Expressions

Complex Fractions

Quadratic Equations

Building the Equation of the line

Graphing Lines

Graphing Inequalities

Absolute Value Inequalities

Absolute Value Equations

Functions

System of Equations

Word Problems

Radical Expressions

Quadratic Functions

Practice Pert Tests

Evaluating Expressions

Simplify Expressions

Exponential Expressions

Factoring Polynomials

Factoring Part 2

Factoring Special Cases

Solving Equations

Translating into numerical expressions

Inequalities

Rational Expressions

Complex Fractions

Quadratic Equations

Building the Equation of the line

Graphing Lines

Graphing Inequalities

Absolute Value Inequalities

Absolute Value Equations

Functions

System of Equations

Word Problems

Radical Expressions

Quadratic Functions

Practice Pert Tests

Functions

A function is a relation that assigns to each input number EXACTLY ONE output number. F(X) or G(X) or H(X) is the same as "Y"

For example if we have a function:

F(X) = 3X²-5 and we need F(2) , that means that in every X you need to substitute it for a 2.

F(2) = 3(2)²-5= 3(4) -5 = 12 -5 = 7, therefore when X= 2,

then F(x)= 7 or Y=7

Let's practice:

If F(X)= 4X + 5, what is F(3) ?

F(3) = 4(3) + 5= 12 + 5= 17

When X=3, then Y= 17

What is F(-1) ?

F(-1) = 4(-1) + 5 = -4 + 5= 1

Translation: when X= -1 then Y= 1

A function is a relation that assigns to each input number EXACTLY ONE output number. F(X) or G(X) or H(X) is the same as "Y"

For example if we have a function:

F(X) = 3X²-5 and we need F(2) , that means that in every X you need to substitute it for a 2.

F(2) = 3(2)²-5= 3(4) -5 = 12 -5 = 7, therefore when X= 2,

then F(x)= 7 or Y=7

Let's practice:

If F(X)= 4X + 5, what is F(3) ?

F(3) = 4(3) + 5= 12 + 5= 17

When X=3, then Y= 17

What is F(-1) ?

F(-1) = 4(-1) + 5 = -4 + 5= 1

Translation: when X= -1 then Y= 1